Enhancing Power Generation: PIV Analysis of Flow Structures’ Impact on Concentrated Solar Sphere Parameters - Hassan Abdulmouti (Energies)
The flow velocity field of the oil-filled acrylic solar sphere is assessed using flow visualization, which includes image processing and Particle Image Velocimetry (PIV) measurements. The temperature, sphere size, and thickness all have an impact on the generated convection flow. The acrylic sphere, a contemporary concentrated photovoltaic technology, collects solar energy and concentrates it into a small focal region. This focus point is positioned precisely above a multi-junction apparatus that serves as an appliance for concentrator cells. Instead of producing the same amount of electricity as a typical photovoltaic panel (PV), this gadget can generate an enormous power rate directly. There are numerous industrial uses for acrylic spheres as well. This study paper aims to examine the flow properties inside a sphere and investigate the impact of the sphere’s temperature, size, and thickness on the fluid motion’s flow velocity. Furthermore, the goal of this research is to elucidate the correlation between these variables to enhance power-generating performance by achieving higher efficiency. The findings demonstrated that the flow structure value is greatly affected by the sphere size, thickness, and temperature. It is discovered that when the spherical thickness lowers, the velocity rises. As a result, the sphere performs better at lower liquid temperatures (35–40 °C), larger sizes (15–30 cm diameter), and reduced acrylic thickness (3–4 mm), leading to up to a 23% increase in power output and a 35–50% rise in internal flow velocity compared to thicker and smaller configurations. Therefore, reducing the sphere thickness by 1 mm results in approximately a 10% increase in average flow velocity at the top of the sphere, corresponding to an increase of about 0.0001 m/s. Notably, the sphere with a 3 mm thickness demonstrates superior power and efficiency compared to other thicknesses. As the sphere’s thickness decreases, the solar sphere’s output power and efficiency rise. The amount of sunlight absorbed by the acrylic photons increases with decreasing acrylic layer thickness; hence, the greater the output power, the higher the efficiency that follows.